PENGGEREK BUAH KAKAO, Conopomorpha cramerella Snellen (TEKNIK PENGENDALIANNYA YANG RAMAH LINGKUNGAN) - Alam Anshary (Universitas Tadulako, 2009)
Predator Dolichoderus thoracicus is a highly potential and has sound prospect in the future as biological control agent against cocoa pod borer (CPB), Conopomorpha cramerella because D. thoracicus function as a predator on cocoa plantation. This research aimed to determine: (a) effective technique of the predator D. thoracicus application in artificial nest established at people cocoa plantation, (b) level of cocoa bean damage, (c) distribution pattern of D. thoracicus, (d) cocoa production analysis result. Research consisted of several phases including setting up artificial nest in cocoa plantation, recording data of cocoa pod borer attack level and analysing the cocoa production. Results showed that exploiting D. thoracic us could reduce the CPB attack by 8.28%, lower the percentage of bean damage by 25.36%, and reduce the loss of cacao bean weight by 16.14%